"'Aint Never Done Anything but Sing": Understanding Betsey through Her Canary. Issue 1 (23rd December 2020) - Dillashaw, Hannah Claire
Abstract: The protagonist in Mary Wilkins Freeman's short story "A Poetess" has a complex relationship with her poetry and how others perceive it. This relationship can be analyzed and understood through the actions of her pet canary and how it behaves in certain instances.